John Murtagh's patient education - Murtagh, John , 1936- (North Ryde, N.S.W. : McGraw Hill Education, 2012)
John Murtagh's Patient Education is the essential aid for doctors in practice, general practice nurses, medical students, pharmacists and consumers needing accurate information in an age of internet selfishness. First published in 1992 and now in its sixth edition, it is the proven international standard for patient education material. -- Provided by publisher
1. Marriage -- 2. Pregnancy and postnatal care -- 3: Children's health -- 4: Adolescent health -- 5: Women's health -- 6: Men's health -- 7: The elderly -- 8: Prevention -- 9: Infections -- 10: Eye disorders -- 11: Musculoskeletal disorders -- 12: Common general problems
Includes index
Keywords: Family medicine; Patient education; Child Welfare -- handbooks; Patient Education -- handbooks; Infection -- Handbooks; Musculoskeletal Diseases -- handbooks